2018
DOI: 10.1186/s12870-018-1383-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of seedling root traits reveals the association of root trait with other agronomic traits in maize

Abstract: BackgroundRoot systems play important roles in crop growth and stress responses. Although genetic mechanism of root traits in maize (Zea mays L.) has been investigated in different mapping populations, root traits have rarely been utilized in breeding programs. Elucidation of the genetic basis of maize root traits and, more importantly, their connection to other agronomic trait(s), such as grain yield, may facilitate root trait manipulation and maize germplasm improvement. In this study, we analyzed genome-wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 57 publications
5
28
1
Order By: Relevance
“…The potential of roots to boost crop productivity has been establish in several studies where correlations between root traits and yield have been determined (Bray and Topp, 2018;Robinson et al, 2018;Jia et al, 2019). This close relation is confirmed by the co-ocurrence of QTLs for root traits and grain yield and other agronomic traits associated to productivity in different crops (Maccaferri et al, 2016;Ju et al, 2018). Root traits like deep rooting or root angle seem to increase vegetative growth and subsequent grain filling but are also context dependent.…”
Section: Increased Temperature Associated Root Traitsmentioning
confidence: 83%
“…The potential of roots to boost crop productivity has been establish in several studies where correlations between root traits and yield have been determined (Bray and Topp, 2018;Robinson et al, 2018;Jia et al, 2019). This close relation is confirmed by the co-ocurrence of QTLs for root traits and grain yield and other agronomic traits associated to productivity in different crops (Maccaferri et al, 2016;Ju et al, 2018). Root traits like deep rooting or root angle seem to increase vegetative growth and subsequent grain filling but are also context dependent.…”
Section: Increased Temperature Associated Root Traitsmentioning
confidence: 83%
“…2) suggests presence of quantitative inheritance of the examined root traits and the involvement of multiple loci underlying these traits. Previous studies have reported numerous genetic loci controlling root length and surface area in maize, wheat, and common bean (Bhatta et al, 2019;Ju et al, 2018;Lin et al, 2019;Polania et al, 2017;Wang et al, 2019). The trait distribution patterns generated in this study will serve as a benchmark in future genetic studies seeking to characterize the genetic basis and inheritance of root phenotypes in watermelon.…”
Section: Accessionmentioning
confidence: 99%
“…Germination assays of the 14 inbred lines. The seeds were surface-sterilized as described previously 63 , wiped dry with paper towels, and then stored in gas-tight containers with silica gel beads for three days before the experiments. For the germination assays of the 14 inbred lines under normal conditions or DE3 and BY815 under chemical treatment, the seeds were immersed in distilled water, 100 µM 1-aminocyclopropane-1-carboxylic acid (ACC) (Sigma-Aldrich, St. Louis, MO), 100 μM silver nitrate (Ag + ) (Sigma-Aldrich), or 10 μM aminoethoxyvinylglycine (AVG) (Sigma-Aldrich) in Petri dishes containing two sheets of moist filter papers on the bottom and two layers of wet gauze on top of the seeds.…”
Section: Methodsmentioning
confidence: 99%
“…Methods for the evaluation of three traits in the DE3 × BY815 RIL population and the two parental lines. The seeds were surface-sterilized as described previously 63 , wiped dry with paper towels, and then stored in gas-tight containers with silica gel beads for three days before the experiments. For each sample, the weight (g) of 20 dry seeds was determined.…”
Section: Methodsmentioning
confidence: 99%